Economic and Political Realities and Models of Territorial Structure Development in the South of the Far East - Koshevaya, Elena S.; Miroshnikova, Tatyana K. (Cuestiones Políticas, 2020)
The economic and political processes taking place in the southern Far East have had a significant impact on the development of the territorial structure. Methodologically, a constructive and comprehensive geopolitical approach was used that allowed a structural evaluation of economic and political realities and their impact on the formation and development of the territorial structure, as well as its various orientations and typologies in the south of the country. Far East. In addition, its focused study allowed to evaluate the economic and political effect of the modernization scenario, to analyze the impact of external and internal economic, political and social realities with a focus on the restructuring and organization of the territorial structure, all of which allowed to identify the main problems of its destabilization and, at the same time, determine the prospects for further growth of the elements of the system to varying degrees, affecting the industrial, transportation, infrastructure and other spheres of the population's life. It is concluded that the dialectical interaction of a set of political and economic realities of transformations and modernizations, internal and external, have configured an arial-nodal / linear-nodal polycentric linear structure in the south of the Far East.